The Effect Of Administration Of Beluntas (Pluchea indica L) Leaf Extract On Albumin Levels And Total White Rat Serum Protein (Rattus novergius) Which Is Induced With E.coli Bacteria - Br Tarigan, Tesya Lonika; Silitonga, Pasar Maulim (Universitas Negeri Medan, 2024)
This study aims to determine whether giving beluntas leaf extract has an effect on albumin levels and total serum protein in white mice induced with E.coli bacteria. RAL was used consisting of 3 treatments and 5 replications. White mice were induced and then given 0.5 ml of extract at a dose of 0.00 mg/kgBW; 300 mg/kgBW; and 600 mg/kgBB. The results showed that administration of the extract had a very significant effect on albumin levels and total serum protein in white mice. Giving the extract at a dose of 600 mg/kgBW gave the highest serum albumin levels but gave the lowest total protein levels. Giving the extract at a dose of 0.00 mg/kgBB; 300 mg/kgBW; and 600mg/kgBW in white mice were induced to give average albumin levels of 2,706 g/dL respectively; 2.844 g/dL; 4.454 g/dL and the mean total serum protein levels were 8.51 g/dL respectively; 8.86 g/dL; 8.8 g/dL.